Strategi Komunikasi Akun Instagram @ Rahasiagadis dalam Pemberdayaan Perempuan Muda: Analisis Uses and Gratifications dan Model RACE - Ika Yuliasari; Mark Mbooh; Nadya Kesyariani; Arun Yudha; Nuraida Nuraida (Jurnal Penelitian Sosial Ilmu Komunikasi, 2025)
This study aims to analyze the role and communication strategies of the Instagram account @rahasiagadis in empowering young women in Indonesia. The research was conducted using a qualitative approach and descriptive methods. Data collection techniques included documentation of Instagram content, non-participatory observation, in-depth interviews with account managers, and literature review. The theoretical reference used to guide the analysis was the Uses and Gratifications model, supported by the RACE (Research-Action-Communication-Evaluation) communication strategy model. The results show that @rahasiagadis has successfully become a digital space for young women, meeting the information, personal identity, and social integration needs of its audience. The @rahasiagadis Instagram account presents a variety of information for young women, has 3.2 million followers, and enjoys repeated access and active audience interaction in the digital space. The novelty in the information content is the consistency of contemporary women's empowerment discourse, including mental health, toxic relationships, body positivity, and gender equality. The @rahasiagadis account has been constructed as social media for empowering women today through community-oriented, participatory communication , and empathetic communication. The conclusion of the study related with the role of  @rahasiagadis account in educating and disseminating current women's issues, including mental health, toxic relationships, body positivity, and gender equality. Education encourages emotional validation and behavioral change in women. The communication strategy is data-driven,  empathetic, responsive to audience opinion, and content evaluation. The communication strategy is supported by designing inclusive and non-doctrinal messages in audio-visual texts on Instagram.